The Study of Motivation in the Suicidal Process: The Motivational Interview for Suicidality - Moselli, Marta; Frattini, Camilla; Williams, Riccardo; Ronningstam, Elsa (Frontiers in Psychiatry, 2021)
In the study of suicide studies have evidenced the necessity to integrate approaches based on the identification of variables as possible predictors of suicidal conduct with a more clinically based approach. A clinical assessment is needed that focuses on the patients’ mental state with respect to thoughts concerning death and suicide. A qualitative assessment of motivations underlying the suicidal process could represent an effective guide for clinicians engaged in the difficult field of preventing adolescents’ suicide. Most instruments investigating the suicidal motivation are self-report, possibly resulting in a lack of sufficiently valid assessment. In the present work, we present the Motivational Interview for Suicidality in Adolescence (MIS-A) aiming at identifying the motivational areas sustaining suicidal ideation and gestures in this phase of development. The identification of the different areas derives from a thorough review of the empirical literature subsequently vetted by expert clinicians who selected specific reasons behind suicidal ideation and gesture. The MIS is a semi-structured clinician-report interview. The interview is composed of seven areas and 14 sub-areas, evaluated on 4-part Likert scale: illness motivated attempts area, chronic presence of internal pessimistic criticism area, sense of defeat and entrapment area, relational area, external motivated crisis area, extreme and unusual cases area, and lack of control area. The path followed in the creation of the MIS reflects both an empirically orientated and a clinically informed approach. Creating this MIS is the first step within a wider research project that will allow one to test the reliability of the instrument.